Left behind - Anderson, Laurie Halse (Anderson, Laurie Halse. Vet volunteers, 2016)
"When Sunita joins Dr. Gabe and another Vet Volunteer on a house call at a local horse farm, she is concerned to discover a lone lamb housed in one of the stalls. She knows that sheep are flock animals, and that without other sheep and lambs around, this little lamb will not thrive. Can she and her fellow Vet Volunteers help educate the owner, and find a new home for it with others of its kind?" --